A transient heat current model for dynamic performance analysis and optimal control of heat transfer system. (December 2019) - He, Ke-Lun; Chen, Qun; Liu, Yi-Tao; Hao, Jun-Hong; Wang, Yi-Fei; Yuan, Ye
Highlights: Propose a transient heat current model for dynamic performance analysis and optimal control. The model reflects the integrated heat transfer and storage laws of heat transfer systems. Deduce state and output matrices to reveal the interrelation of multiple system parameters. Develop an integrated control method to reduce pumping power consumption at unsteady state. Abstract: Taking dynamic characteristic into consideration to realize performance prediction and optimal control of heat transfer systems is significant for energy conservation. This paper first proposes a transient heat current model of heat exchanger to clearly express the relation of different variables at unsteady state. Then, utilizing the topological relations of every heat exchanger in heat transfer systems forms the transient heat current models and derives the integrated constraint equations to reflect the system heat transfer and storage laws, which further offers the state equation and the output equation to reflect the interrelation of different system parameters. Applying these equations yields an integrated control method to realize the optimal control of heat transfer systems by taking the interaction of multiple control variables and objectives into consideration. For a four-loop heat transfer system, the newly proposed integrated control method with optimized intermediate temperatures reduces 25.7% of the total pumping power comparing to that obtained by a traditional local control method with preset intermediate temperatures, which shows the capability and superiority of the newly proposed method.